Self Management Coaching in Improving Discipline of Students SMK Statika Leuwiliang Bogor - Rahmawati Alwi; Siti Shofiatul Qolbiah; Nia Lestari (al-Afkar, Journal For Islamic Studies, 2023)
The purpose of doing this Community Service (PKM) is to assist in the application of self-management in increasing student discipline at SMK Statika Bogor. This Community Service (PKM) was carried out as a form of contribution by the lecturers of the Ummul Quro Al Islami Bogor Institute to serve the community, especially to provide self-management guidance so that students at Statics Vocational High School are more disciplined in learning. The method applied is coaching to students by providing training which is carried out with the stages of identifying first, then conducting socialization and evaluating which then gets the result that after coaching self-management student discipline is in the significant category